Eosinophilic esophagitis and refractory heartburn: Case report and review of literature - Marques,Inês (2012)
Eosinophilic esophagitis is an inflammatory condition in which there is dense eosinophilic infiltration of the esophageal lining epithelium. The adult form has only recently gained recognition as a distinct entity. Because of the reflux-type symptomatology, it is commonly misdiagnosed and treated as severe gastroesophageal reflux disease before an appropriate diagnosis is made. We herein present a case of an asthmatic young woman in whom eosinophilic esophagitis was suspected based on symptoms of gastroesophageal reflux disease refractory to standard medical therapy. Biopsies taken from esophageal normal appearing mucosa were essential to establish the diagnosis. She was successfully treated with swallowed fluticasone. As clinical and pathologic features of gastroesophageal reflux disease and eosinophilic esophagitis may overlap, proper diagnosis requires a keen index of suspicion. Increased awareness of eosinophilic esophagitis is necessary, since treatment with topical steroids may be more effective than acid suppression.